Experimental Study on Directional Shear of Q2 Remolded Loess Considering the Direction of Principal Stress - Wang, Sui; Zhao, Peng; Gao, Zhihua; Zhong, Zuliang; Chen, Bin; Wu, Bo; Sun, Qingjun; Song, Chunxia (Frontiers in Earth Science, 2022)
In order to study the strength and deformation characteristics of Q2 remodeled loess, soil samples from the Lisi area in Shanxi Province were used to investigate the effects of the principal stress axis direction angle α and the medium principal stress coefficient b on the shear and non-coaxial properties of remodeled loess using the hollow cylindrical torsional shear system (GCTS). The study shows that when b is constant, the generalized shear stress ratio decreases with increasing α at 0°-45°, and achieves the minimum value at α=45°; α increases again with increasing principal stress axis direction angle at 45°-90°; When α is 0-45°, the generalized shear stress ratio decreases gradually with the increase of the intermediate principal stress coefficient b .When α is at 60°-90°, the shear strength ratios at different Intermediate principal stress coefficients are shown as follows: strength at b=0.5 > strength at b=1 > strength at b=0. In addition, by defining the degree of strength volatility of this remodeled loess to determine its breaking strain standard, it can be found through comparative analysis that when the generalized shear strain of this remodeled loess is 6.5%, the strength of this remodeled loess has reached more than 90%, so this paper suggests using its generalized shear strain of 6.5% as its breaking strain standard; In addition, when α at 0-45 °, the direction angle of strain increment increases with the increase of the direction angle of principal stress axis, and reaches the peak at 45°; When α at 60° - 90°, the direction angle of strain increment decreases with the increase of the direction angle of the principal stress axis, that is, the non-coaxial characteristics of the remolded loess first increase, then decrease, and gradually tend to be coaxial.